The ECB's role in financial supervision - Karl Whelan (University College Dublin, UCD School of Economics, 2009)
The European Council's decisions to implement the De Larosiere recommendations for a reformed approach to micro-level financial supervision and a new European Systemic Risk Board (ESRB) are to be welcomed. The ECB's central role in the ESRB is also to be welcomed. However, the limited role envisaged for the ESRB means that it may not actually help much in preventing future crises. The ESRB should be given a central role in the implementation of counter-cyclical capital ratios and in promoting (and then overseeing implementation of) other changes such as maximum leverage ratios and limits on non-core funding.
hdl:10197/2613
Keywords: 330